Choice of an antihistamine administration route in the treatment of allergic diseases - L V Luss (Терапевтический архив, 2016)
Allergic diseases (AD) are an interdisciplinary problem in practical health care and characterized by high prevalence, severity, and huge financial costs of their treatment, prevention, and rehabilitation in patients. In this connection, control of allergy symptoms attracts the meticulous attention of physicians of all specialties. The efficiency of pharmacotherapy in clinical practice frequently depends not only on what medication, but also what mode of its delivery (administration) is used. Clinicians are well aware of the fact that oral administration of some drugs, antihistamines in particular, may be lowly effective or ineffective and their parenteral route gives rise to their sufficient clinical effect. This communication presents for general practitioners a pathogenetic rationale for prescribing histamines and indications for their parenteral administration in AD.